Hyperinsulinemic Hypoglycaemia in a Turner Syndrome with Ring (X) - Michela Cappella; Vanna Graziani; Antonella Pragliola; Alberto Sensi; Khalid Hussain; Claudia Muratori; Federico Marchetti (Case Reports in Pediatrics)
Hyperinsulinemic hypoglycaemia (HH) is a group of clinically, genetically, and morphologically heterogeneous disorders characterized by dysregulation of insulin secretion by pancreatic beta cells. HH can either be congenital genetic hyperinsulinism or associated with metabolic disorder and syndromic condition. Early identification and meticulous management of these patients is vital to prevent neurological insult. There are only three reported cases of HH associated with a mosaic, r(X) Turner syndrome. We report the four cases of an infant with a mosaic r(X) Turner genotype and HH responsive to diazoxide therapy.